Penerapan Media Sosial Dalam Pengaduan Dugaan Maladministrasi Pada Ombudsman Ri Perwakilan Sulawesi Selatan - Setiawan, Hardi; Usman, Jaelan; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2022)
This study aimed to find out the application of social media in complaints of alleged maladministration at the RI Ombudsman Representative for South Sulawesi. The method used descriptive qualitative with the number of informants 6 people. The data analysis techniques used data reduction, data exposure and conclusion. Data collection techniques through observation, interviews, and documentation. The results of this study showed that online complaints of alleged maladministration seen from the commitment to resolve complaints were good, but some were still in the process of being completed. The simplicity of the complaint made it much easier for the community to report, it meant that the manager received the complaint controls, followed up and then explained step by step to the community in reporting process. The speed in completing the report was carried out with a predetermined procedure and it had been good because in receiving complaints the ombudsman was able to respond quickly then asked for an explanation of the problems and explained the complaint procedure to the public. Keywords: Complaints, Ombudsman